Parametric study of different control strategies for organic rankine cycle recovering waste heat - Bateman, Jared Maurice (2019)
The objective of this project is to study the effect of transient behaviour of various control strategies for a PI controller in ORC systems to optimize waste heat recovery by analysing dynamic system simulations on Dymola, where the hot gas side of the evaporator is imposed with a ramp and sinusoidal variation which would mimic real-life fluctuations in waste heat source arising from scenarios such as changes in an engine load.